Formulasi Sediaan Lip Balm dari Ekstrak Buah Murbei (Morus Alba L.) Sebagai Pewarna Alami - Fitri Hafidhah Uluhidayah; Liandhajani Liandhajani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Using lip balm is very easy to apply to the lips and lip balm can also moisturize and brighten the lips. Lip balm is resistant to body temperature, and is harmless and smooth when applied so that the lips are cared for and healthy. The anthocyanin contained in mulberry fruit has the potential to act as a purplish red natural dye depending on the presentation of the mulberry fruit extract used, which has the positive side of being an antioxidant and scavenger of free radicals. The aim of this research was to determine the formulation and stability of the lip balm preparation formula using mulberry fruit extract (Morus alba L.) as a natural coloring with an accelerated stability test using 4 cycles. Using this research method, material testing includes organoleptic tests, homogeneity tests, melting point tests, pH tests, spreadability tests, adhesion tests, spreadability tests, stability tests, and hedonic tests, as well as preparation irritation tests. Based on the results of research on making lip balm from mulberry fruit extract as a natural coloring, it can be formulated in lip balm preparations, however if 20% extract is used it can affect the physical properties of the lip balm preparation, neither the 5%, 10%, 15% and 20% formulas. irritation was found.